2014
DOI: 10.1634/theoncologist.2014-0345
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial Evaluating the Efficacy and Safety of Efavirenz in Metastatic Castration-Resistant Prostate Cancer

Abstract: Background. Preclinical studies demonstrated that nonnucleoside reverse transcriptase inhibitors used for the treatment of HIV could antagonize tumor development. This led us to assess the efficacy of efavirenz in patients with metastatic castration-resistant prostate cancer (mCRPC) in a multicenter phase II study. Methods. We used a Simon two-stage design and a 3-month prostate-specific antigen (PSA) nonprogression rate of 40% as a primary objective. Patients received 600 mg efavirenz daily with the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…-34.5.) (130). Despite the fact that primary objective of the trial was not met, it was striking to note a high variability in plasma concentrations of the drug that was actually comparable with previously reported concentrations in HIV patients ranging from 125 to 15,230 ng/ml (131,132).…”
Section: The Clinical Evaluation Of Efavirenz In Mcrpc Patientssupporting
confidence: 64%
See 1 more Smart Citation
“…-34.5.) (130). Despite the fact that primary objective of the trial was not met, it was striking to note a high variability in plasma concentrations of the drug that was actually comparable with previously reported concentrations in HIV patients ranging from 125 to 15,230 ng/ml (131,132).…”
Section: The Clinical Evaluation Of Efavirenz In Mcrpc Patientssupporting
confidence: 64%
“…Before the approval of efavirenz for HIV treatment, a phase I study established the safety of 1800 mg/day single dosage and 1200 mg/day repeated dosage in healthy patients. In our phase II study, 13 patients received a dose of 1200 mg/day without any serious adverse event (Grade 3 or 4), indicating that higher dosages are well tolerated in prostate cancer patients despite their relatively advanced age (130). Indeed, although the median age of the treated patients was higher compared to other efavirenz toxicity studies, the safety profile of this NNRTI was confirmed and no new or unexpected adverse events were noticed, confirming that it is overall well tolerated with most adverse events being of grade 1 or 2.…”
Section: The Clinical Evaluation Of Efavirenz In Mcrpc Patientsmentioning
confidence: 81%
“…So far there exists only one clinical trial in which NNRTIs were used to treat cancer in HIV-negative patients [45]. Fifty-three patients with metastatic castration-resistant prostate cancer were treated with EFV 600mg once daily.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of understanding of how L1 inhibition regulates cellular processes, Efavirenz is currently undergoing a phase II trial in castration-resistant metastatic prostate cancer [66]. Importantly, this trial has revealed that patients with the highest plasma concentrations of efavirenz (>3000 ng/ml) showed less progression of their cancers compared with patients who received suboptimal concentrations of Efavirenz.…”
Section: Preclinical Studies Of L1 Blockage and Prospects For L1 Drugmentioning
confidence: 99%